Milly, Molly and the jungle gym - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
Milly and Molly convert their school into a biscuit factory, showing how success can come from co-operation. Includes teaching guide. Suggested level: junior